1995
DOI: 10.1002/jcp.1041630207
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear translocation of prolactin: Collaboration of tyrosine kinase and protein kinase C activation in rat Nb2 node lymphoma cells

Abstract: Recent evidence has suggested that prolactin (PRL), internalized by lactogen-dependent Nb2 lymphoma cells, is actively translocated to the nucleus where it binds to PRL receptors. Moreover, the mitogenic action of PRL in these cells has been separately linked to protein tyrosyl phosphorylation and activation of protein kinase C (PKC). Therefore, the coupling of PRL internalization and nuclear translocation to the activation of these signal transduction pathways was investigated. Results from control experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Intranuclear Stat5 binds to consensus Stat5 response elements, resulting in the transactivation of numerous PRL-specific genes, of which ␤-casein is the most extensively studied (9). This Stat5 transcriptional activation can be cooperatively enhanced by the glucocorticoid receptor (GR) and C͞EBP␤ (10-12).While the above-mentioned pathways are all associated with PRL-induced signaling, activation of the PRL receptor is also associated with ligand internalization via an endosomal-like pathway across the endoplasmic reticulum (ER) and nuclear envelopes (13,14). The phenomenon of protein retrotransport was initially characterized through the study of retrotranslocated viral and bacterial proteins and peptides destined for presentation on the major histocompatibility complex (15-18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intranuclear Stat5 binds to consensus Stat5 response elements, resulting in the transactivation of numerous PRL-specific genes, of which ␤-casein is the most extensively studied (9). This Stat5 transcriptional activation can be cooperatively enhanced by the glucocorticoid receptor (GR) and C͞EBP␤ (10-12).While the above-mentioned pathways are all associated with PRL-induced signaling, activation of the PRL receptor is also associated with ligand internalization via an endosomal-like pathway across the endoplasmic reticulum (ER) and nuclear envelopes (13,14). The phenomenon of protein retrotransport was initially characterized through the study of retrotranslocated viral and bacterial proteins and peptides destined for presentation on the major histocompatibility complex (15-18).…”
mentioning
confidence: 99%
“…While the above-mentioned pathways are all associated with PRL-induced signaling, activation of the PRL receptor is also associated with ligand internalization via an endosomal-like pathway across the endoplasmic reticulum (ER) and nuclear envelopes (13,14). The phenomenon of protein retrotransport was initially characterized through the study of retrotranslocated viral and bacterial proteins and peptides destined for presentation on the major histocompatibility complex (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…A number of studies suggest the involvement of the PI pathway in PRL action in a variety of tissues including cultured mammary tissues, Nb2 node lymphoma cells, hypothalamic slices and astrocytes (Rillema et al 1988, DeVito et al 1993, Doppler 1994, Rao et al 1995. Activation of this pathway initiates the hydrolysis of phosphatidylinositol 4,5-bisphosphate to inositol trisphosphate and diacylglycerol.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies performed on mammary gland cells , Banerjee & Vonderhaar 1992, Fan & Rillema 1993, Nb 2 node lymphoma cells , Rao et al 1995), astrocytes (DeVito et al 1993 and hypothalamus (DeVito et al 1991) demonstrated that PKC is an important component of signal-transduction pathways induced by PRL. PKC is a family of serine/ threonine protein kinases consisting of multiple isoforms different in their structure, substrate specificity and regulatory characteristics (Nishizuka 1992, Liu 1996.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation